Factors contributing to work fatigue among nurses at hospital: A study on the impact of work attitudes, shift schedules, and sleep quality - Diana, Tyra Septi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Fatigue is an essential body protection mechanism, preventing further damage and allowing recovery after rest. In work, especially in the hospital environment, fatigue can affect the performance and well-being of medical personnel, including nurses. This study aims to identify and analyze factors associated with work-related fatigue among Dr. Adjidarmo Regional Hospital nurses. The main focus of this study includes the relationship between gender, length of service, work attitude, shift schedule, and sleep quality on the level of fatigue experienced by nurses. Method: This study adopted a cross-sectional design targeting a population of 256 nurses who are actively practicing at Dr Adjidarmo Regional Hospital. The study sample consisted of 75 respondents selected using a random sampling method. Data was collected through questionnaire-based interviews that accessed information from secondary and primary sources. The data obtained were analyzed univariate and bivariate to determine the prevalence and significant relationship between the variables studied and work-related fatigue. Findings: Univariate analysis revealed that out of 75 respondents, 54.7% reported experiencing moderate work-related fatigue. Demographic distribution showed that 74.7% of respondents were female, 81.3% had worked for five years or more, 50.7% showed risky work attitudes, 29.3% worked night shifts, and 52.0% reported poor sleep quality. The results of the bivariate analysis showed a significant relationship between work attitudes (P-value = 0.000), shift schedules (P-value = 0.002), and sleep quality (P-value = 0.000) with the level of work-related fatigue. Conclusion: Based on these findings, it is recommended that shift schedules be distributed evenly during the third shift to reduce nurse fatigue. In addition, stretching exercises and physical activity during work breaks should be encouraged to improve nurses' well-being and reduce fatigue-related problems. This intervention aims to improve nurses' working conditions, which can improve patient care quality and reduce fatigue's negative impact on work performance. Originality/Novelty: This study offers new insights into factors contributing to work-related burnout among nurses, focusing on specific variables such as work attitudes, shift schedules, and sleep quality. The study identifies significant correlations that have not been widely explored in the context of a regional hospital in Indonesia. By providing practical recommendations for redistributing shift schedules and promoting stretching exercises, this study contributes to the development of evidence-based intervention strategies to address burnout in the hospital workplace.